Attitudes of Orthodontic Patients to Glove and Mask Wearing - Aslıhan M. Ertan Erdinç; Banu Dinçer (Galenos Yayinevi, 2005)
In order to determine the perception and awareness of orthodontic patients of glove and mask wearing by orthodontists, a study was designed including a questionnaire completed by 356 patients (191 girls and 165 boys). The ages of the patients were between 9 and 36.9 years with an average of 15 years. Patients were asked to answer the 9 questions in the form. The patients were divided into 3 groups as juvenile (9-12 years), adolescence (12-18 years) and adult (18 and older) in order to determine the correlation between age and answers. The answers of the questions did not show any statistically significant difference between girls and boys. According to the results, 96.3 % (n=343) of the patients considered that orthodontists should routinely wear glove, 84.3 % (n=300) of the patients believed that glove were essential for both patients and doctors' protection. 65.5 % (n=233) of the patients pointed out they would not attend an orthodontist who doesn't wear glove. However, 34.5 % (n=123) of the patients stated that they would attend an orthodontist even if he / she doesn't wear glove. 92.1 % (n=328) of the patients specified that orthodontists should change glove between patients and only 5 patients found it acceptable to wash glove protected hands between patients. 73.3 % (n=261) of the patients demanded their doctors to wear masks. However, 29 % of children, 34.9 % of adolescents and 48 % of the adults stated that they would not attend an orthodontist who doesn't wear masks. The increase in demand of mask wearing from early ages to adulthood was found statistically significant and demonstrated that awareness of the patients increased with age. The increase in prevalence of certain infectious diseases like AIDS and HBV points out the clinical significance of glove and mask wearing by orthodontists. Patients are demanding from their doctors to use glove and mask during treatment in order to obey cross-infection control rules.